The analysis of primary school student’s motivation toward science learning - Nasir, Nur Indah Ririn Fitriani; Arifin, Slamet; Damopolii, Insar (Journal of Research in Instructional, 2023)
This research aims to analyze primary school students' motivation to learn science. Differences in student grades and gender were also examined in this research. The research has used survey methods. The survey was carried out on 97 students at one of the elementary schools in Malang City. The students who participated were those in grades 4, 5 and 6. A questionnaire containing 35 statement items measured students' motivation toward science learning. The analysis uses ANOVA to measure differences in motivation based on grade, gender, and interactions between grade and gender. There is no influence of grade and gender on students' motivation to learn science. On average, students' science learning motivation is good. Female students dominate the overall motivation score (M), active learning strategies (ALS), self-efficacy (SE), performance goal (PG), and science learning value (SLV), while Achievement goal (AG) and learning environment stimulation (LES) dominate the male student scores. The student's PG was weak. This indicates that students study science not to improve their performance but to get attention and be considered the best by others.